Efficacy and safety of hyaluronic-polidocanol foam in sclerotherapy for head and neck venous malformations - Sun, Zhaoyang; Liu, Yiran; Chen, Anwei; Wang, Tao; Liu, Shaohua (Frontiers in Neurology, 2024)
Foam sclerotherapy is currently the first-line treatment for venous malformations (VMs). Hyaluronic acid-polidocanol (HA-POL) foam has been used in the treatment of head and neck VMs recently; however, its clinical efficacy and safety have yet to be further evaluated, and the impact of age and other related factors on its safety is still unclear.To assess the efficacy and safety of HA-POL foam in the treatment of head and neck VMs.We performed a single-center retrospective review of all patients with VMs involving the head and neck region undergoing HA